Crystal facet engineering of α-Fe₂O₃: Boosting tetracycline photodegradation via synergistic highly active {001} and co-existing facets - Conghui Wang; Xun Luo; Qingqing Ning; Yang Liu; Yuxuan Wu; Binhan Ye; Zichen Yu; Zhenxing Liu; Mingdi Wu; Shengtao Wu; Xiaoyu Cao (Journal of Environmental Chemical Engineering, 2026)

In situ white-to-brown reprogramming to induce adipocyte thermogenesis by engineered bacteria for breast cancer immunotherapy - Lulu An; Zichen Yang; Rongjie Li; Jianwei Cheng; Yanni Cai; Haiqing Dong; Yiqiong Liu; Yan Li; Yongyong Li (Chemical Engineering Journal, 2026)

Optimization and characterization of a low-toxicity trans-anethole nanoemulsion for controlling the soil-borne bacterial pathogen Ralstonia solanacearum - Yao Wang; Yonghao Liu; Lei Yang; Zichen Li; Mengxiao Xie; Deping Ke; Gui Gao; Zhijun Chen; Jiaxi Yuan; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

Hierarchical in situ biomineralization-enhanced electroactive biofilm for high-efficiency antibiotic degradation - Zichen Li; Qi Qiu; Yan Feng; Shuming Yang; Yanzhen Yu (Bioresource Technology, 2026)

Preparation and properties of an in-situ sealing and water retention double-network gel for inhibiting coal spontaneous combustion - Jiangle Wu; Caiping Wang; Jun Deng; Yang Xiao; Yi Lu; Zichen Shi; Zujin Bai; Jiuxiao Lu (Journal of Environmental Chemical Engineering, 2026)

Reconstruction of temperature and soot volume fraction in C2H4/NH3 diffusion flame based on the improved two-color method integrated with the absorption coefficient ratio model - Zijun Tian; Shu Zheng; Yu Yang; Weiguang Cai; Zichen Lv; Yao Kong; Hao Liu; Qiang Lu (Fuel, 2026)

The interdecadal Pacific oscillation drives an extratropical tripole pattern in northern hemisphere summer rainfall anomalies - Zichen Tang; Song Yang; Noel Keenlyside; Lingling Suo; Hanjie Fan; Qingquan Li; Guillaume Gastineau; Tian Tian (Atmospheric Research, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

A hybrid method coupling physical process-driven model with generative deep learning for probabilistic flood forecasting - Xuesong Yang; Bin Xu; Jingwen Liu; Junliang Jin; Ran Mo; Xinrong Wang; Zichen Ren; Yao Liu; Yuchen Shi; Qisheng Zhou; Ping-an Zhong (Journal of Hydrology, 2026)

Managing street-tree health under rapid urbanization: Relative roles of street context and root-zone conditions in a subtropical city - Wenting Wang; Min Wu; Hai Yan; Ying Chen; Zichen Zhao; Lin Zhu; Jiangnan Shi; Renwu Wu; Fan Yang; Zhiyi Bao (Journal of Environmental Management, 2026)

Mixed ion–electron conductor assembled from sulfonated chitosan and rGO for accelerating Desolvation kinetics and inducing 3D nucleation in Li–S batteries - Jiajun Chen; Jianying Zhang; Yixian Xiao; Yinuo Yu; Yunxiao Ren; Shuoning Zhang; Xinzhao Xia; Wenting Xie; Jiale Liu; Zichen Wang; Lanying Zhang; Wei Hu; et al. (Chemical Engineering Journal, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Schnurri-3 inhibitor-modified 3D-printed hierarchical porous scaffold promoted vascularized bone regeneration via enhanced BMSC-EC crosstalk - Suru Liu; Shichong Qiao; Zichen Tang; Xiaomeng Zhang; Yulin Yang; Xindi Wei; Junyu Shi; Yingxin Gu; Meifei Lian; Hongchang Lai (Chemical Engineering Journal, 2026)

Tracking the pattern of material metabolism and environmental impacts of phosphogypsum utilization in China - Huimin Hou; Yumeng Yang; Zichen Di; Haibin Wu; Fangqin Cheng; He Xu (Journal of Cleaner Production, 2026)

Impact of potassium ion concentration on the aquatic ecological risk of monovalent thallium leached from lithium slag - Gejun Dai; Qian S. Liu; Yuchen Wang; Zichen Kuang; Xiaoxi Yang; Qunfang Zhou; Guibin Jiang (Science China Earth Sciences, 2026)

Hybrid high-dimensional vine copula–Bayesian network framework for flood risk analysis in reservoir–lake systems: Addressing multisource uncertainties - Xuesong Yang; Bin Xu; Huili Wang; Xinman Qin; Xinrong Wang; Zichen Ren; Yao Yao; Siying Zhou; Yao Liu; Ping Chang (Environmental Modelling & Software, 2026)

Air temperature differences and view factor influences between sidewalks and roadways in urban streets: A case study in Hangzhou, China - Zichen Zhao; Hai Yan; Huaizhen Zhu; Xinge Nan; Renwu Wu; Wenting Wang; Wei Yang; Lin Zhu; Jiangnan Shi; Fan Yang; Zhiyi Bao (Building and Environment, 2026)

Green flexible job-shop scheduling considering transportation time and machine multi-rotation speeds - Minghai Yuan; Zhen Zhang; Zichen Li; Yang Ye; Fengque Pei; Wenbin Gu (Swarm and Evolutionary Computation, 2025)

An initial subsystem stiffness-integrated seismic performance optimization approach for super high-rise frame-core tube structures using generalized models - Xiao Lai; Zheng He; Jian Yang; Zichen Li (Soil Dynamics and Earthquake Engineering, 2025)

Insights into ensemble learning based data-driven model for prediction of chemical safety production accidents - Weiwei Gao; Jixing Yang; Yudong Fang; Wei Guo; Zichen Wang; Xiaochun Chen (Process Safety and Environmental Protection, 2025)

Enhanced efficiency of bacteria-algae symbiotic biofilm reactors in treating coal chemical wastewater: Mechanisms and microbial dynamics - Jingxin Shi; Yuanyuan Yang; Zichen Zhu; Shengyang Li; Haifeng Zhuang (Journal of Environmental Chemical Engineering, 2025)

Determination of yeast β-glucan content in composite yeast culture by enzymatic hydrolysis HPLC method - Xiaojie Zhang; Zixuan Xu; Zichen Yun; Lulu Bai; Xiaohui Xu; Qifei Luo; Dorjgoo Purevtsogt; Lan Yang; Dacheng Liu (Food Chemistry, 2025)

Dynamic sealing mechanisms of drilling fluid in fractured coalbed methane formations: a coupled CFD-DEM numerical study - Zichen Han; Xianyu Yang; Ni Ren; Jiwei Song; Meng Zhao; Man Xue; Mengjia Liang; Xinmin Yan; Chunzheng Jin; Guosheng Jiang; Jihua Cai (Computers and Geotechnics, 2025)

Spectral feature variations of low-iron olivine under intense pulse-laser irradiations - Zichen Wei; Yan Zhuang; Hao Zhang; Pengfei Zhang; Yang Li; Menghua Zhu; Te Jiang; Ronghua Pang (Icarus, 2025)

Exploring the influence of hydrological indicators on flow regimes through a data-driven modeling approach in the Huai river basin, China - Qing Wei; Peipei Chen; Zichen Jia; Yongqi Chen; Zhanzhan Yuan; Huijin Zhang; Ju Yang; Bin Niu; Zuxin Xu (Environmental Research, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Do healthier trees cool better? Assessing the impact of street tree health on urban thermal regulation and pedestrian comfort - Wenting Wang; Min Wu; Hai Yan; Yijuan Sang; Renwu Wu; Wei Yang; Zichen Zhao; Xinge Nan; Lin Zhu; Zhiyi Bao (Building and Environment, 2025)

Strongly enhanced topological quantum phases in dual-surface AlO -encapsulated MnBi2Te4 - Zichen Lian; Yongqian Wang; Yongchao Wang; Liangcai Xu; Xinlei Hao; Shuai Yang; Bohan Fu; Jinsong Zhang; Chang Liu; Yayu Wang (Science Bulletin, 2025)

Potential buffering capacity of naturally distributed carbonate minerals against future rises in atmospheric CO2 and coastal acidification: the Yellow Sea and three major estuaries in China - Wenting Shi; Weidong Zhai; Shu Yang; Congcong Guo; Zichen Liu; Hongmei Chen (Marine Environmental Research, 2025)

A survey of antibiotic contamination in tap water and associated health risks in China - Yuanping Wang; Yi Wang; Ke Zhao; Jiaqi Liu; Zichen Yang; Qifan Yang; Wenjuan Cong; Hexing Wang; Yue Chen; Qingwu Jiang (Environmental Pollution, 2025)

Spatiotemporally-graded BHP/G@met scaffold system enables sequential angiogenesis-osteogenesis coupling for accelerated bone regeneration - Han Zhang; Shuqing Chen; Guodong Zhang; Yongbin Wang; Zichen Cui; Fei Chen; Yukun Du; Guanghui Gu; Tianyu Bai; Changlin Lv; Wenkang Yang; Shiqi Xu; et al. (Chemical Engineering Journal, 2025)

Hetero-structured hydrogel with transition layer: Achieving synergistic sensing-actuating integration for intelligent ship - Bingchen Zhou; Tianzong Jiang; Yanqi Yin; Zewei Sun; Zichen Lu; Shili Gai; He Ding; Piaoping Yang (Chemical Engineering Journal, 2025)

Global health impacts of PAHs based on high-resolution modeling by dynamic simulation and relative emission downscaling - Zichen Wu; Xueshun Chen; Yuanlin Wang; Wenyi Yang; Yang Wang; Zhe Wang; Huansheng Chen; Lianfang Wei; Wending Wang; Huiyun Du; Zhuoran Wang; Ying Wei; et al. (Atmospheric Environment, 2025)

Effects of Cardiac Rehabilitation Combined with Enhanced External Counterpulsation on Heart Rate Variability and Autonomic Nervous Function in Chronic Heart Failure - Yiliang Yan; Zichen Han; Bowen Zhou; Kui Li; Jintao Hu; Sigong Yang; Jun Zhang; Xuemin Hu (Cardiovascular Toxicology, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

Mask-GK: An efficient method based on mask Gaussian kernel for segmentation and counting of grape berries in field - Canchen Yang; Tianyu Geng; Jian Peng; Chun Xu; Zichen Song (Computers and Electronics in Agriculture, 2025)

Reinforcement learning event-triggered energy-based control for unmanned surface vessel with disturbances - Chengxing Lv; Ying Zhang; Zichen Wang; Jian Chen; Zhibo Yang; Haisheng Yu (Ocean Engineering, 2025)

Green low-carbon approach for the preparation of solid waste-based geopolymer: One-part geopolymer vs. two-part geopolymer - Muyang Huang; Zhiming Qiu; Shenxu Bao; Yimin Zhang; Zichen Zhou; Siyuan Yang; Xuan Ke (Journal of Environmental Chemical Engineering, 2025)

Simulation and prediction of PM2.5 concentrations and analysis of driving factors using interpretable tree-based models in Shanghai, China - Qing Wei; Yongqi Chen; Huijin Zhang; Zichen Jia; Ju Yang; Bin Niu (Environmental Research, 2025)

Genetically engineered hybrid membrane-coated nanoparticles enable triple activation of dendritic cells for synergistic bladder cancer immunotherapy - Jian Wu; Zhiqiang Chen; Haojie Shang; Yonghua Tong; Wen Deng; Yu He; Xiaozhuo Ba; Zichen Zhong; Yongke Bai; Tao Ye; Xiaoqi Yang; Kehua Jiang; et al. (Chemical Engineering Journal, 2025)

Applicability of the allergen Ana o 3 in the construction of a cashew nut allergy paradigm in BALB/c mice - Youdou Cheng; Fangfang Min; Tian Yu; Xintong Yang; Yang Wu; Zichen Yin; Hongbing Chen; Jinyan Gao; Yong Wu (Food Bioscience, 2025)

Design, synthesis, and evaluation of antitumor activity of quinazoline derivatives containing different terminal segments of basic amine groups - Shihao Wang; Zichen Yang; Dongling Gu; JiaHui Han; Hongjing Chen; Hao Wang; JiaXin Zheng; Hongmin Liu; Yu Ke; Qiurong Zhang (Medicinal Chemistry Research, 2025)

Quasi-harmonic analysis of fortnightly suspended sediment response to semi-diurnal tidal currents - Zichen Zhu; Bingchen Liang; Bin Chen; Bo Yang; Wanqing Chi; Hao Xu; Zejian Hu (Frontiers in Marine Science, 2024)
Introduction The suspended sediment concentration (SSC) is an important consideration in marine engineering. Sediment movement characteristics can be studied by considering the fortnightly behavior of SSC. However, this consideration currently lacks accurate mathematical representation. Method In this study, a computationally efficient mathematical model capable of providing analytical solutions for predicting SSC based on resuspension, deposition, and advection was developed to further investigate the mathematical interpretation of fortnightly SSC behavior in coastal areas dominated by M2, S2, O1, K1, M4 and MS4 tides. The model decomposed the SSC into 35 quasi-harmonic terms as well as two terms with fortnightly period. Result The model was applied at five observation sites in the Bohai Sea, Yellow Sea and East China Sea, China, and validated to be able to reproduce the fortnightly variation of SSC. The results show that the primary fortnightly SSC term was generated by the combined action of M2 and S2 tidal currents and had a tidal frequency of 1.0159 °/h, which was equal to the difference between the frequencies of the two partial tides. Discussion The resuspension properties only affected the amplitude of the fortnightly SSC term but did not affect the phase. The deposition properties affected both amplitude and phase. The quasi-harmonic analysis indicates that in certain shallow sea areas with strong nonlinear tidal interactions, the amplitude of the M4 tidal elevation can influence the mean SSC, while the amplitude of the MS4 tidal elevation can affect the fortnightly SSC amplitude. As the simplified model is based on certain assumptions, the application conditions of the quasi-harmonic analytical solution include an approximate reciprocating flow pattern, a tidal range significantly smaller than the water depth. Our results provide a mathematical solution for the fortnightly evolution of suspended sediment.

Nitrogen deposition enhances accumulation of microbial and plant-derived carbon in forest soils: a global meta-analysis - Chenying Wang; Xiaoyan Li; Meng Zhang; Zichen Han; Yun Xia; Pingping Lian; Liuming Yang; Kai Yue; Yuexin Fan (Plant and Soil, 2024)

Response of heterocyst differentiation of Dolichospermum to different forms of nitrogen deficiency - Zichen Liu; Fazhi Xie; Liya Wang; Li Yu; Xiaoli Shi; Zhen Yang; Min Zhang (Harmful Algae, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Nanofiber aerogel with layered array with structure coupled photothermal/magnetothermal effect for continuous seawater desalination - Zichen Yu; Tingting Fan; Yang Liu; Bowen Yang; Luyao Wang; Fang Yin; Yuan Gao; Yun-Ze Long (Chemical Engineering Journal, 2024)

Design, synthesis and biological evaluation of novel pyrimidine-phenylsulfonylfuroxan hybrids - Dongling Gu; Shihao Wang; Zichen Yang; Hongjing Chen; Jiahui Han; Lingling Chi; Fuqiang Yu; Hao Wang; Jiaxin Zheng; Peirong Zhao; Hongmin Liu; Yu Ke; et al. (Medicinal Chemistry Research, 2024)

Source identification of nitrate in groundwater of an agro-pastoral ecotone in a semi-arid zone, northern China: Coupled evidences from MixSIAR model and DOM fluorescence - Anqi Chen; Yao Du; Zichen Wang; Xiaoliang Sun; Rui Xu; Yaojin Xiong; Liangping Yang; Junting Liu; Yiqun Gan (Applied Geochemistry, 2024)

Glutamine metabolism in fluorosis: Integrated metabolomics and transcriptomics analysis - Yue Ba; Shu Niu; Zichen Feng; Shuo Yang; Shuiyuan Yu; Chaofan Shi; Xuecheng Jiao; Guoyu Zhou; Fangfang Yu (Science of The Total Environment, 2024)

Modification of glycosyltransferase SrUGT76G1 based on computer-aided screening of mutation sites for efficient synthesis of rebaudioside M - Liang Zhao; Yaqi Liu; Yingnan Li; Fei Pan; Ting Yang; Zichen Yang; Xiang Lv; Lei Zhao; Chengtao Wang (Food Bioscience, 2024)

Contrast in Secondary Organic Aerosols between the Present Day and the Preindustrial Period: The Importance of Nontraditional Sources and the Changed Atmospheric Oxidation Capability - Yingchuan Yang; Wenyi Yang; Xueshun Chen; Jiawen Zhu; Huansheng Chen; Yuanlin Wang; Wending Wang; Lianfang Wei; Ying Wei; Qian Ye; Huiyun Du; Zichen Wu; et al. (Advances in Atmospheric Sciences, 2024)

Probability map-based grape detection and counting - Canchen Yang; Tianyu Geng; Jian Peng; Zichen Song (Computers and Electronics in Agriculture, 2024)

Numerical simulation of soot and NO formation in DME/gasoline laminar co-flow diffusion flames - Shu Zheng; Zichen Lv; Yu Yang; Hao Liu; Qiang Lu (Fuel, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Healable and multi driving mode soft actuator enabled by disulfide-bonded liquid crystal elastomers - Shuoning Zhang; Zichen Wang; Jianying Zhang; Jiale Liu; Chang Sun; Shengyu Qin; Yunxiao Ren; Lanying Zhang; Wei Hu; Huai Yang (Chemical Engineering Journal, 2024)

A facile and on-demand optimizing strategy for polyurethane elastomers via programmable hydrogen bonding - Zichen Bai; Xiaodong Li; Tianhao Wu; Hao Jiang; Xudong Zhang; Lichen Zhang; Yi Yang; Shuang Liu; Lisha Lei; Ningning Song; Zhengdi Wang; Xing Su; et al. (Chemical Engineering Journal, 2024)

Carbon quantum dots assisted BiFeO3@BiOBr S-scheme heterojunction enhanced peroxymonosulfate activation for the photocatalytic degradation of imidacloprid under visible light: Performance, mechanism and biotoxicity - Sai Bai; Ting Lv; Miaomiao Chen; Chang Li; Zichen Wang; Xinyao Yang; Tianjiao Xia (Science of The Total Environment, 2024)

Source and health risk of urinary neonicotinoids in Tibetan pregnant women - Yuanping Wang; Yangzong Gesang; Yi Wang; Zichen Yang; Ke Zhao; Jiaqi Liu; Chunxia Li; Luobu Ouzhu; Hexing Wang; Yue Chen; Qingwu Jiang (Chemosphere, 2024)

Reconstructed β-NiOOH enabling highly efficient and ultrastable oxygen evolution at large current density - Runzhe Chen; Yunkai Yang; Wei Wu; Suhao Chen; Zichen Wang; Yu Zhu; Niancai Cheng (Chemical Engineering Journal, 2024)

Highly efficient Cr (VI) removal from electroplating wastewater by regenerable copper sulfides: Mechanism and magical induction effect for Cr resource recovery - Chen Ma; Mengle Liu; Zichen Yang; Qianxian Zheng; Jian Mei; Shijian Yang (Environmental Research, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Bubble-driven piezo-activation of E-MoS2/PVDF piezoelectric microcapsule for antibiotic degradation with ultralow energy consumption - Bingjie Huo; Jingxue Wang; Zichen Wang; Xiaowen Zhang; Jingwei Yang; Yinglong Wang; Jianguang Qi; Wei Ma; Fanqing Meng (Journal of Cleaner Production, 2023)

Assessment of Atmospheric Reanalysis Data Based on Buoy Observations over the Tropical Western Indian Ocean in 2019 - Yulan Luo; Lin Liu; Oloo Paul; Sagero Philip; Kuiping Li; Yang Yang; Qinglei Su; Qiuchi Li; Zichen Miao (Journal of Ocean University of China, 2023)

Giant nonlocal edge conduction in the axion insulator state of MnBi2Te4 - Yaoxin Li; Chang Liu; Yongchao Wang; Zichen Lian; Shuai Li; Hao Li; Yang Wu; Hai-Zhou Lu; Jinsong Zhang; Yayu Wang (Science Bulletin, 2023)

Exposure of Tibetan pregnant women to antibiotics in China: A biomonitoring-based study - Yuanping Wang; Yue Chen; Yangzong Gesang; Zichen Yang; Yi Wang; Ke Zhao; Minghui Han; Chunxia Li; Luobu Ouzhu; Jiwei Wang; Hexing Wang; Qingwu Jiang (Environmental Pollution, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Enhanced cyanogen chloride formation after UV/PS and UV/H2O2 pre-oxidation and chlorination in natural river water - Jie Xu; Yang Guo; Qian Yang; Xueling Bai; Runhua Lu; Menghui Liu; Zichen Kuang; Luo Zhang; Jing Li (Journal of Environmental Sciences, 2023)

A Data-Driven Model for Ice-Breaking Resistance of Structure Based on Non-Smooth Discrete Element Method and Artificial Neural Network Method - Zhe Sun; Yongjin Qiu; Biye Yang; Zichen Jia; Guiyong Zhang; Zhi Zong (Journal of Marine Science and Engineering, 2023)
In this paper, a data-driven model based on the Non-smooth Discrete Element Method (NDEM) and Artificial Neural Network Method (ANN) is proposed for the computation of the ice-breaking resistance of the structure. The idea of so-called “meta-modelling”, which means establishing an Artificial Neural Network (ANN) model based on a pre-computed ice failure database to avoid the time-consuming direct resolving of the ice fracture process, was integrated in the non-smooth discrete element method (NDEM). The developed model was validated by simulating the ice-breaking process of the cone structure, and the computational results match well with the experimental ones in the literature. After that, the effects of various parameters on the ice-breaking resistance were analyzed by the developed model. It was found that the factors that have great influence on the resistance of cone structure in level ice condition are the cone angle, navigation velocity and ice thickness.

Detection of melamine by using carboxyl-functionalized Ag-COF as a novel SERS substrate - Zichen Yang; Chaoqun Ma; Jiao Gu; Yamin Wu; Chun Zhu; Lei Li; Hui Gao; Wenzhi Yin; Zirui Wang; Guoqing Chen (Food Chemistry, 2023)

Oxygen activity excited thiophene-diketopyrrolopyrrole-based organic molecules as anode for lithium-ion batteries with enhanced interfacial storage capacity and long cycling capability - Zichen Xu; Shengxian Hou; Zhiqiang Zhang; Jing Yang; Yingzhi Cheng; Pengfei Zhou; Hongtao Lin; Shuhai Chen; Jin Zhou; Shuping Zhuo (Chemical Engineering Journal, 2023)

Efficient electrochemical CO2 reduction to CO by metal and nitrogen co-doped carbon catalysts derived from pharmaceutical wastes adsorbed on commercial carbon nanotubes - Yang Gang; Boyang Li; Siyuan Fang; John Pellessier; Lingzhe Fang; Fuping Pan; Zichen Du; Yun Hang Hu; Tao Li; Guofeng Wang; Ying Li (Chemical Engineering Journal, 2023)

Circulation Driven by Multihump Turbulent Mixing Over a Seamount in the South China Sea - Ruijie Ye; Xiaodong Shang; Wei Zhao; Chun Zhou; Qingxuan Yang; Zichen Tian; Yongfeng Qi; Changrong Liang; Xiaodong Huang; Zhiwei Zhang; Shoude Guan; Jiwei Tian (Frontiers in Marine Science, 2022)
Turbulent mixing above rough topography is crucial for the vertical motions of deep water and the closure of the meridional overturning circulation. Related to prominent topographic features, turbulent mixing not only exhibits a bottom-intensified vertical structure but also displays substantial lateral variation. How turbulent mixing varies in the upslope direction and its impact on the upwelling of deep water over sloping topography remains poorly understood. In this study, the notable multihump structure of the bottom-intensified turbulent diffusivity in the upslope direction of a seamount in the South China Sea (SCS) is revealed by full-depth fine-resolution microstructure and hydrographic profiles. Numerical experiments indicate that multihump bottom-intensified turbulent mixing around a seamount could lead to multiple cells of locally strengthened circulations consisting of upwelling (downwelling) motions in (above) the bottom boundary layer (BBL) that are induced by bottom convergence (divergence) of the turbulent buoyancy flux. Accompanied by cyclonic (anticyclonic) flow, a three-dimensional spiral circulation manifests around the seamount topography. These findings regarding the turbulent mixing and three-dimensional circulation around a deep seamount provide support for the further interpretation of the abyssal meridional overturning circulation.

Piezo1 mediates endothelial atherogenic inflammatory responses via regulation of YAP/TAZ activation - Ying Yang; Danyang Wang; Chunxiao Zhang; Wenqing Yang; Chao Li; Zichen Gao; Ke Pei; Yunlun Li (Human Cell, 2022)

Risk factors for recurrent positive results of the nucleic acid amplification test for COVID-19 patients: a retrospective study - Wanwan Yi; Xuan Long; Jin Liu; LiShuai Shi; Zichen Chen; Jing Yang; Ziyu Yang; Zhongwei Lv; Hengwei Fan (Human Cell, 2021)
Positive retests of COVID-19 represent a public health concern because of the increased risk of transmission. This study explored whether factors other than the nucleic acid amplification test (NAAT) contribute to positive retest results. Patients with COVID-19 admitted to the Guanggu district of the Hubei Maternal and Child Health Hospital between February 17 and March 28, 2020, were retrospectively included. The patients were grouped into the negative ( n = 133) and positive ( n = 51) retest groups. The results showed that the proportion of patients presenting with cough was higher ( P < 0.001) and the proportion of patients with dyspnea was lower ( P = 0.018) in the positive than in the negative retest group. The positive retest group showed shorter durations between symptom onset and hospitalization ( P < 0.001) and symptom onset and the first positive NAAT ( P = 0.033). The positive retest group had higher basophil counts ( P = 0.023) and direct bilirubin ( P = 0.032) and chlorine concentrations ( P = 0.023) but lower potassium concentrations ( P = 0.001) than the negative retest group. Multivariable regression analysis showed that coughing (OR = 7.59, 95% CI 2.28–25.32, P = 0.001) and serum chloride concentrations (OR = 1.38, 95% CI 1.08–1.77, P = 0.010) were independently associated with a positive retest result. Coughing and serum chloride concentrations were independent risk factors for positive NAAT retest results. Patients with a hospital stay of < 2 weeks or a short incubation period should stay in isolation and be monitored to reduce transmission. These results could help identify patients who require closer surveillance.

Mitigation of Cd accumulation in rice with water management and calcium-magnesium phosphate fertilizer in field environment - Wenxuan Luo; Shaona Yang; Mohammad Aman Khan; Jiawei Ma; Weijie Xu; Yaqian Li; Zichen Xiang; Gaoqi Jin; Junwei Jia; Bin Zhong; Lili Duan; Youwei Zhu; et al. (Environmental Geochemistry and Health, 2020)

Characterization and genome sequencing of a novel T7-like lytic phage, kpssk3, infecting carbapenem-resistant Klebsiella pneumoniae - Yunlong Shi; Yu Chen; Zichen Yang; Yulong Zhang; Bo You; Xinzhu Liu; Ping Chen; Meixi Liu; Cheng Zhang; Xiaoqiang Luo; Yajie Chen; Zhiqiang Yuan; et al. (Archives of Virology, 2020)

Characterization and genome annotation of a newly detected bacteriophage infecting multidrug-resistant Acinetobacter baumannii - Zichen Yang; Xinzhu Liu; Yunlong Shi; Supeng Yin; Wei Shen; Jing Chen; Yu Chen; Yajie Chen; Bo You; Yali Gong; Xiaoqiang Luo; Cheng Zhang; et al. (Archives of Virology, 2019)

Epigenetic Signature of Chronic Cerebral Hypoperfusion and Beneficial Effects of S-adenosylmethionine in Rats - Xiangmei Wu; Jing Sun; Xiaowen Zhang; Xiaona Li; Zichen Liu; Qinglin Yang; Liang Li (Molecular Neurobiology, 2014)

Hydrophobic calcium carbonate: an option for the value-added conversion of wastes resulting from biodiesel production - Hong Lei; Xue Chen; Shuang Guan; Yang Liu; Xuefeng Ding; Zichen Wang (Environmental Chemistry Letters, 2011)